Capacity Matching Based Model for Protected Left Turn Phases Design of Adjacent Signalized Intersections Along Arterial Roads - Wei Wu; Wanjing Ma; Kejun Long (Promet - Traffic&Transportation, 2015)
A protected left turn phase is often used at intersections with heavy left turns. This may induce a capacity gap between adjacent intersections along the arterial road among which only parts of intersection are with protected left turn phase. A model for integrated optimization of protected left turn phases for adjacent intersections along the arterial road is developed to solve this problem. Two objectives are considered: capacity gap minimization and capacity maximization. The problems are formulated as Binary-Integer-Linear-Programs, which are solvable by standard branch-and-bound routine. A set of constraints have been set up to ensure the feasibility of the resulting optimal left turn phase type and signal settings. A field intersections group of the Wei-er Road of Ji’nan city is used to test the proposed model. The results show that the method can decrease the capacity gap between adjacent intersections, reduce the delay as well as increase the capacity in comparison with the field signal plan and signal plan optimized by Synchro. The sensitivity analysis has further demonstrated the potential of the proposed approach to be applied in coordinated design of left turn phases between adjacent intersections along the arterial road under different traffic demandpatterns.